KERJA SAMA INDONESIA - JEPANG DALAM PENGIRIMAN PERAWAT MEDIS DAN PENGASUH LANSIA MELALUI INDONESIA - JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) PERIODE 2017 - 2020 - Chatrien Cissilia Lolyta, (2021)
This research is about Indonesia - Japan cooperation in sending nurses and careworkers through the collaboration of IJEPA during 2017 - 2020 in the MNP sub-committee. It is analyzed using migration theory and the concepts of bilateral cooperation and national interest. The research method used is a qualitative method with a descriptive analysis approach. The author uses interviews and literature study to collect data. In this research, the author wants to show that this cooperation can run optimally if every obstacle can be overcome properly. Not only describing the existing obstacles, but also explaining the solutions provided by both the Government of Indonesia and Japan to overcome the problems that occurred. The delivery of health workers is necessary to fulfill the national interest of each country. Indonesia needs jobs to absorb health workers in order to find work, while Japan needs a lot of health workers to care for people with an average elderly population. Obstacles that hinder this collaboration include language barriers, obstacles when carrying out contracts in Japan, as well as delays in the delivery of the 13th and subsequent batches due to the Covid-19 pandemic. The solutions provided to optimize the cooperation are the extension of the duration of the residence permit in Japan, Indonesia's collaboration with the Fukuoka Perfecture Medical Association (FPMA) to expand work opportunities in Japan and maximize distance learning while waiting for the placement period.